2023
DOI: 10.1002/anie.202215460
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biochemical Characterization, and Genetic Encoding of a 1,2,4‐Triazole Amino Acid as an Acetyllysine Mimic for Bromodomains of the BET Family

Abstract: Lysine acetylation is a charge-neutralizing post-translational modification of proteins bound by bromodomains (Brds). A 1,2,4-triazole amino acid (ApmTri) was established as acetyllysine (Kac) mimic recruiting Brds of the BET family in contrast to glutamine commonly used for simulating this modification. Optimization of triazole substituents and side chain spacing allowed BET Brd recruitment to ApmTricontaining peptides with affinities similar to native substrates. Crystal structures of ApmTri-containing pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Recently, another stable mimic of acetyllysine, 1,2,4-triazole amino acid (ApmTri), has been site-specifically incorporated into proteins by WT MmPylRS in mammalian cells. 178 The ApmTri-containing proteins were shown to have similar binding affinity with other proteins to that of acetyllysinecontaining proteins. All these above-mentioned acetyllysine mimics offer alternative approaches when acetyllysine residues undergo rapid deacetylation in living cells.…”
Section: Lysine Acetylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, another stable mimic of acetyllysine, 1,2,4-triazole amino acid (ApmTri), has been site-specifically incorporated into proteins by WT MmPylRS in mammalian cells. 178 The ApmTri-containing proteins were shown to have similar binding affinity with other proteins to that of acetyllysinecontaining proteins. All these above-mentioned acetyllysine mimics offer alternative approaches when acetyllysine residues undergo rapid deacetylation in living cells.…”
Section: Lysine Acetylationmentioning
confidence: 99%
“…In this study, TFAcK-containing proteins were also demonstrated to be resistant to sirtuin deacetylases. Recently, another stable mimic of acetyllysine, 1,2,4-triazole amino acid (ApmTri), has been site-specifically incorporated into proteins by WT Mm PylRS in mammalian cells . The ApmTri-containing proteins were shown to have similar binding affinity with other proteins to that of acetyllysine-containing proteins.…”
Section: Lysine Modificationsmentioning
confidence: 99%
“…In addition to the natural modification, lysine acetylation mimics, such as thioacetylation, trifluoroacetylation, and 1,2,4‐triazole, have also be designed and integrated into proteins in the forms of ε‐ N ‐thioacetyl‐lysine (TAcK; Venkat et al, 2017), ε‐ N ‐trifluoroacetyl‐lysine (TFAcK; Zhang et al, 2018), and 1,2,4‐triazole amino acid (ApmTri; Kirchgäßner et al, n.d.), respectively (Figure 2a). All of these modifications are non‐hydrolyzable and resistant to deacetylases, providing alternative approaches to access stable and homogenous proteins bearing acetylation mimics.…”
Section: Lysine Modificationsmentioning
confidence: 99%